2011
DOI: 10.1177/0748730410388746
|View full text |Cite
|
Sign up to set email alerts
|

Pigment-Dispersing Factor Affects Nocturnal Activity Rhythms, Photic Entrainment, and the Free-Running Period of the Circadian Clock in the Cricket Gryllus bimaculatus

Abstract: Pigment-dispersing factor (PDF) is a neuropeptide widely distributed in insect brains and plays important roles in the circadian system. In this study, we used RNA interference to study the role of the pigment-dispersing factor (pdf) gene in regulating circadian locomotor rhythms in the cricket, Gryllus bimaculatus. Injections of pdf double-stranded RNA (dspdf) effectively knocked down the pdf mRNA and PDF peptide levels. The treated crickets maintained the rhythm both under light-dark cycles (LD) and constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Moreover, pdf mRNA expression levels showed no diurnal rhythmicity under either long or short days in the head of R. pedestris. Although diurnal and circadian expression of pdf mRNA were reported for A. mellifera (Sumiyoshi et al, 2011), pdf mRNA levels and cytoplasmic PDF immunoreactivity showed no prominent oscillation in many other insects (Park and Hall, 1998;Park et al, 2000;Matsushima et al, 2003;Hassaneen et al, 2011). However, circadian oscillations of immunoreactivity have been reported in the terminals of s-LN v s in D. melanogaster (Park et al, 2000).…”
Section: Research Articlementioning
confidence: 88%
See 3 more Smart Citations
“…Moreover, pdf mRNA expression levels showed no diurnal rhythmicity under either long or short days in the head of R. pedestris. Although diurnal and circadian expression of pdf mRNA were reported for A. mellifera (Sumiyoshi et al, 2011), pdf mRNA levels and cytoplasmic PDF immunoreactivity showed no prominent oscillation in many other insects (Park and Hall, 1998;Park et al, 2000;Matsushima et al, 2003;Hassaneen et al, 2011). However, circadian oscillations of immunoreactivity have been reported in the terminals of s-LN v s in D. melanogaster (Park et al, 2000).…”
Section: Research Articlementioning
confidence: 88%
“…In G. bimaculatus, the decrease of PDF immunoreactivity by RNAi was much slower than that of pdf mRNA levels, and complete disappearance was not observed during the 20 days after dsRNA injection, although pdf RNAi decreased PDF immunoreactivity to below the detection limit within 10 days in B. germanica (Lee et al, 2009;Hassaneen et al, 2011). The long lifetime of the PDF peptide would explain the high PDF immunoreactivity in the fibres of PDFMe neurons, even 20 days after the cell bodies were completely removed.…”
Section: Research Articlementioning
confidence: 94%
See 2 more Smart Citations
“…The output pathway controlling overt rhythms also remains to be explicated. Cerebral PDF neurons are apparently involved in the clock's output pathway, because RNAi of pdf gene reduced the nocturnal activity with reduced amount of PDF (Hassaneen et al, 2011). PDF is more strongly involved in control of overt activity rhythms in Drosophila and cockroaches.…”
Section: Future Perspectivesmentioning
confidence: 99%